Early pragmatic language difficulties in siblings of children with autism: implications for DSM‐5 social communication disorder?. (15th October 2014) - Miller, Meghan; Young, Gregory S.; Hutman, Ted; Johnson, Scott; Schwichtenberg, A.J.; Ozonoff, Sally
Abstract : Background: We evaluated early pragmatic language skills in preschool‐age siblings of children with autism spectrum disorder (ASD), and examined correspondence between pragmatic language impairments and general language difficulties, autism symptomatology, and clinical outcomes. Methods: Participants were younger siblings of children with ASD (high‐risk, n = 188) or typical development (low‐risk, n = 119) who were part of a prospective study of infants at risk for ASD; siblings without ASD outcomes were included in analyses. Pragmatic language skills were measured via the Language Use Inventory (LUI). Results: At 36 months, the high‐risk group had significantly lower parent‐rated pragmatic language scores than the low‐risk group. When defining pragmatic language impairment (PLI) as scores below the 10 th percentile on the LUI, 35% of the high‐risk group was identified with PLI versus 10% of the low‐risk group. Children with PLI had higher rates of general language impairment (16%), defined as scores below the 10 th percentile on the Receptive or Expressive Language subscales of the Mullen Scales of Early Learning, relative to those without PLI (3%), but most did not evidence general language impairments. Children with PLI had significantly higher ADOS scores than those without PLI and had higher rates of clinician‐rated atypical clinical best estimate outcomes (49%) relative to those without PLI (15%). Conclusions: Pragmatic language problems are present in some siblings of children with ASD as early as 36 months of age. As the new DSM‐5 diagnosis of Social (Pragmatic) Communication Disorder (SCD) is thought to occur more frequently in family members of individuals with ASD, it is possible that some of these siblings will meet criteria for SCD as they get older. Close monitoring of early pragmatic language development in young children at familial risk for ASD is warranted.